Galectin-3, Carotid Plaque Vulnerability, and Potential Effects of Statin Therapy. Issue 1 (January 2015) - Kadoglou, N.P.E.; Sfyroeras, G.S.; Spathis, A.; Gkekas, C.; Gastounioti, A.; Mantas, G.; Nikita, K.S.; Karakitsos, P.; Liapis, C.D.
Abstract : Objectives: Galectin-3, a member of galectines, a family of β-galactoside-specific lectins, has been reported to propagate vascular inflammation. The role of galectin-3 in carotid atherosclerosis is controversial. The aim of this study was to investigate the relationship of galectin-3 with plaque vulnerability in patients with high grade carotid stenosis. Methods: This was a cross sectional study of patients undergoing carotid endarterectomy (CEA). Carotid plaques obtained from 78 consecutive patients (40 symptomatic [SG], 38 asymptomatic [AG]) undergoing CEA were histologically analyzed for galectin-3, macrophages (CD68) and laminin. Pre-operatively the biochemical profile and plaque echogenicity (gray-scale median, GSM) score were determined. Results: There were no significant differences in clinical and demographic parameters between SG and AG ( p > .05). The SG had a lower GSM score (44.21 ± 18.24 vs. 68.79 ± 28.79, p < .001) and a smaller positive stained area for galectin-3 (4.89 ± 1.60% vs. 12.01 ± 5.91%, p < .001) and laminin (0.88 ± 0.71% vs. 3.46 ± 2.12%, p < .001) than the AG. On the other hand, intra-plaque macrophage content was increased in SG ( p < .001). For the whole cohort, symptomatic status was independently associated with intra-plaque contents of both galectin-3 (OR = 0.634, p < .001), and GSM score (OR = 0.750, p < .001). Notably, patients on long term statin treatment had elevated galectin-3 and lowered macrophage intra-plaque concentrations compared with those on short term treatment ( p < .05). Conclusions: A low galectin-3 intra-plaque concentration seems to correlate with clinically and ultrasonically defined unstable human carotid plaques. Long term statin treatment may induce increase of intra-plaque galectin-3 concentration mediating plaque stabilization.